Investigation of finish cut of microelectrodischarge milling for nanosurface finish - Ali, Mohammad Yeakub; Mehfuz, R. (A V S AMER INST PHYSICS, USA, 2009)
In this article, the machining conditions to achieve nanometric surface roughness in finish cut microelectrodischarge milling were investigated. For a constant gap voltage, the effect of feed rate and capacitance was studied on average surface roughness (Ra) and maximum peak-to-valley roughness height (Ry). Statistical models were developed using a three-level, two-factor experimental design. The developed models minimized Ra and Ry by desirability function approach. Maximum desirability was found to be more than 98%. The minimum values of Ra and Ry were 23 and 173 nm, respectively, for 1.00 μm s−1 feed rate and 0.01 nF capacitance. Verification experiments were conducted to check the accuracy of the models, where the responses were found to be very close to the predicted values. Thus, the developed models can be used to generate nanometric level surface finish, which are useful for many applications in microelectromechanical systems.